Changing Patterns of Residential Centrality : Population and Household Shift in Large Canadian CMAs, 1971-1996. - Bunting, Trudi; Filion, Pierre; Priston, Heath (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 2000)
The research focuses on Canadian CMAs with populations of 500 000 or greater over the period 1971-1996. It uses population density gradients and enumeration of population and household shift to assess changing patterns of residential centrality over the twenty-five year period. Results indicate that all of the CMAs examined have experienced continued outward dispersion, some more so than others. When population change in core and inner-city zones is examined in conjunction with reduced density gradients, only one Canadian metropolitan area, Vancouver, shows indisputable signs of strong recentralization. Three other CMAs, Toronto, Victoria and Calgary, also experience some re-population of their central parts, while Montréal and Québec City are shown to maintain what we call "residual" centrality. However, when recentralization is gauged using household enumeration instead of population counts, all of the places studied show evidence of new housing production in the central city. The answer to the central question regarding residential centrality is thus a mixed one, yes and no. Overall, we conclude that there is a direct link between evolutionary patterns within the national urban System and changes observed in residential centrality. Whatever the measure used, highest rates of recentralization accompany strong metropolitan-wide growth over the 25-year period.